Heterostructure material and preparation method and application thereof
By loading potassium ion conductors on sodium-based layered oxides to form heterostructures, the problem of insufficient performance of sodium-based layered oxide positive electrode materials is solved, significantly improving the magnification and cycling performance of sodium-ion batteries, and achieving higher electrochemistry performance.
Patent Information
- Application Number
- CN202411359766.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-07
AI Technical Summary
The cycling and capacity performance of sodium-based layered oxide positive electrode materials is low. Due to the large volume and mass of sodium ions, the electron conduction and ion conduction rate are low, and its theoretical capacity and cycling performance cannot be fully exerted.
Using heterostructured materials of composite sodium-based layered oxide and potassium ion conductors, the potassium ion conductor is loaded on the surface of sodium-based layered oxides, forming sodium-potassium solid solution, improving the ratio and circulation performance of the material, and forming it through high-temperature sintering. Heterostructure, enhancing ion channel connectivity and chemical stability.
It significantly improves the rate performance and cycling performance of sodium ion batteries, improves the conductivity and chemical stability of the materials, and enhances the electrochemical performance.
Smart Images

Figure CN119275263A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy, and in particular relates to a heterogeneous structure material and a preparation method and application thereof. Background Art
[0002] As people's awareness of ecological and environmental protection increases, the sustainable development and storage of energy are highly valued by countries around the world. In today's world where problems such as shortage of traditional fossil energy and energy security are emerging one after another, the development of sustainable energy is particularly important. Among various energy storage systems, electrochemical energy storage systems (EES) are considered to be an effective way to balance the cycle characteristics of renewable energy due to their long service life, low cost, low investment, and easy installation. Secondary battery energy storage has great potential in electrochemical energy storage. Among them, lithium-ion batteries dominate the energy storage market due to their high theoretical specific capacity and specific energy density. However, due to objective factors such as lithium extraction technology, geographical environment, and traffic conditions, lithium resources are limited and unevenly distributed, and lithium resources are consumed in many aspects. The development of the power battery field is limited by lithium resources. The insufficient supply of lithium resources has led to an increase in prices, and the continued rise in lithium prices will accelerate the process of companies looking for more cost-effective alternatives. In order to alleviate this problem, relevant fields have proposed to replace lithium with abundant elements such as sodium (Na), potassium (K), magnesium (Mg), aluminum (A1), and calcium (Ca) to prepare a new generation of low-cost, environmentally friendly secondary ion batteries. Among them, sodium-ion batteries have received increasing attention and support.
[0003] Sodium-based layered oxide cathode material is one of the key materials for sodium-ion batteries. Similar to lithium cobalt oxide and ternary structures of lithium batteries, the layered oxide structure has good ion channels. Although there are certain shortcomings in cycle performance, the average maturity is relatively high. Transition metal oxide NaXMeO2 is an embedded or intercalated compound, which theoretically has a high discharge specific capacity. However, since the volume and mass of sodium ions as carriers are larger than those of lithium ions, the electronic and ion conductivity of this type of material is low, so that the final material cannot fully exert its theoretical capacity and cycle performance.
[0004] It can be seen that it is urgent to find a solution that can improve the cycle performance and capacity performance of sodium-based layered oxide positive electrode materials. Summary of the invention
[0005] In order to solve all or part of the above technical problems, the present invention provides the following technical solutions:
[0006] One of the purposes of the present invention is to provide a heterostructure material, the heterostructure material comprising a composite sodium-based layered oxide and a potassium ion conductor, the potassium ion conductor being supported on the surface of the nano-based layered oxide, and a sodium-potassium solid solution being formed at the composite interface between the two;
[0007] The chemical formula of the sodium-based layered oxide is Na x Ni a Fe b Mn c M d O2, wherein a+b+c+d=1, 0.7≤x≤1.0, 0.1≤a≤0.4, 0.1≤b≤0.4, 0.2≤c≤0.6, 0.01≤d≤0.2, M includes any one or more of K, Li, Ca, Cu, Mg, Zn, Sr, B, Y, Sn, Al, Nb, Ti, Zr, W, Sr, Co, and Mo; the chemical formula of the potassium ion conductor is K 1+z Fe2(MoO4) 2-z (PO4) 1+z , 0≤z≤1.
[0008] The potassium ion conductor in the heterostructure material provided by the present invention has a wide alkali metal ion channel and high conductivity. The heterostructure material formed by the composite of the potassium ion conductor and the sodium-based layered oxide exhibits better rate performance and cycle performance than the simple sodium-based layered oxide. The sodium-potassium solid solution formed at the composite interface of the potassium ion conductor and the sodium-based layered oxide can connect the ion channels of the two, thereby significantly improving the rate performance and cycle performance of the battery when it is used as an active material. In addition, the potassium ion conductor composited on the surface of the sodium-based layered oxide also has a certain coating effect, which inhibits the contact of the sodium-based layered oxide with the outside world, thereby further improving its chemical stability and cycle performance.
[0009] In some embodiments, the mass proportion of the potassium ion conductor in the heterostructure material is 0.1% to 5.0%. The present invention has systematically studied and found that when the mass proportion of the potassium ion conductor is within the above range, the rate and cycle performance of the heterostructure material are better. If the content of the potassium ion conductor is low, the improvement of the rate cycle performance is not obvious. If the content of the potassium ion conductor is high, the sodium-potassium solid solution layer and the coating layer will be too thick, thereby reducing the capacity release of the sodium ion battery.
[0010] In some embodiments, the sodium-potassium solid solution accounts for 0.02% to 1.5% by mass in the heterostructure material.
[0011] In some embodiments, the heterostructure material is spherical particles with a diameter of 4 to 16 um, which include spherical sodium-based layered oxides with a particle size of 4 to 15 um, and potassium ion conductors loaded on the surface of the sodium-based layered oxides, and a sodium-potassium solid solution is generated at the composite interface of the sodium-based layered oxides and the potassium ion conductors.
[0012] A second object of the present invention is to provide a method for preparing a heterogeneous structure material, the method comprising:
[0013] Providing a sodium-based layered oxide precursor;
[0014] drying a mixed solution containing a potassium source, an iron source, a molybdenum source and a phosphorus source to obtain a gel;
[0015] The gel and the sodium-based layered oxide precursor are mixed and crushed to obtain a first mixture;
[0016] The first mixture is subjected to a first sintering in an oxygen-containing atmosphere to form a heterogeneous structure material composed of a sodium-based layered oxide and a potassium ion conductor, wherein the heterogeneous structure material includes a sodium-potassium solid solution formed at a composite interface of the sodium-based layered oxide and the potassium ion conductor.
[0017] In some embodiments, the preparation method of the sodium-based layered oxide precursor includes: subjecting a first mixed reaction system containing a nickel source, a manganese source and an iron source to a co-precipitation reaction to obtain a nickel-iron-manganese-based precursor; and under inert atmosphere conditions, subjecting a second mixture containing the nickel-iron-manganese-based precursor, an M source and a sodium source to a second sintering to obtain the sodium-based layered oxide precursor.
[0018] In some embodiments, the preparation method of the sodium-based layered oxide precursor includes: subjecting a second mixed reaction system containing a nickel source, a manganese source, an iron source, and an M source to a coprecipitation reaction to obtain a nickel-iron-manganese-based precursor doped with an M element; and subjecting a third mixture containing the nickel-iron-manganese-based precursor doped with the M element and a sodium source to a third sintering under an inert atmosphere to obtain the sodium-based layered oxide precursor. In this method, the third mixture may also contain an M source, for example, different M sources are introduced during the coprecipitation reaction and the third sintering process to achieve doping of different doping elements.
[0019] In some embodiments, the M source is used to provide a doping element M, and the doping element M includes any one or more combinations of K, Li, Ca, Cu, Mg, Zn, Sr, B, Y, Sn, Al, Nb, Ti, Zr, W, Sr, Co, and Mo elements, but is not limited thereto.
[0020] In some embodiments, the M source includes any one or more combinations of sulfates, hydrochlorides, nitrates, carbonates, acetates, oxides, sulfides, nitrides or hydroxides of the doping element M, but is not limited thereto.
[0021] In some embodiments, the sodium source includes any one or more combinations of anhydrous sodium carbonate, sodium carbonate monohydrate, sodium carbonate decahydrate, sodium bicarbonate or sodium sulfate, but is not limited thereto.
[0022] In some embodiments, the nickel source, iron source, manganese source, and M source are in accordance with the chemical formula of sodium-based layered oxide Na x Ni a Fe b Mn c M d The molar ratio of Ni, Fe, Mn and M in O2 is weighed, where a+b+c+d=1, 0.7≤x≤1.0, 0.1≤a≤0.4, 0.1≤b≤0.4, 0.2≤c≤0.6, and 0.01≤d≤0.2.
[0023] In some embodiments, the process conditions of the second sintering and the third sintering include: a sintering temperature of 300 to 600° C. and a sintering time of 4 to 16 hours.
[0024] The nickel source, iron source and manganese source used in the present invention can be raw materials commonly used in the prior art for preparing nickel-iron-manganese-based materials. The coprecipitation method used is a conventional process in the prior art, and the present invention does not impose any particular limitation on this.
[0025] In some embodiments, the inert atmosphere includes one or more of nitrogen, argon, and helium, and the flow rate of the inert atmosphere is 1 to 30 L / min.
[0026] In some embodiments, the mixed solution further includes 0.01-0.5 wt % of concentrated nitric acid.
[0027] In some embodiments, the preparation method of the mixed solution includes: dispersing the potassium source, iron source, molybdenum source and phosphorus source in a solvent, and then adding concentrated nitric acid with a concentration of 68.0wt% to 88.0wt% in batches under stirring, and the amount of concentrated nitric acid added is 0.01 to 0.5wt% of the mixed solution, so that the potassium source, iron source, molybdenum source and phosphorus source are completely dissolved to obtain the mixed solution.
[0028] In some embodiments, the drying dries the water content in the gel to 0.1-3 wt %.
[0029] In some embodiments, the process conditions of the first sintering include: a sintering temperature of 800-1000° C. and a sintering time of 6-20 hours.
[0030] In some embodiments, the pulverizing is performed by a powdering machine with a rotation speed of 10000 to 60000 r / min, and the pulverizing time is 20 to 60 s.
[0031] In some embodiments, the mass ratio of the sodium-based layered oxide precursor to the gel in the first mixture is 100:0.2 to 100:10. If the gel content is high, the potassium ion conductor coating layer formed will be too thick, affecting the capacity and rate performance of the battery; if the gel content is too low, an effective sodium-potassium solid solution cannot be formed or the formed sodium-potassium solid solution is small, and the battery rate performance is not significantly improved.
[0032] In some embodiments, the oxygen-containing atmosphere includes air or oxygen, and the flow rate of the oxygen-containing atmosphere is 1 to 30 L / min.
[0033] In some embodiments, the potassium source includes one or more of potassium nitrate, potassium carbonate, potassium hydroxide, potassium bicarbonate, potassium acetate, potassium dihydrogen phosphate, potassium citrate, and potassium oxalate, but is not limited thereto.
[0034] In some embodiments, the iron source includes one or more of ferric nitrate, ferric acetate, ferric sulfate, and ferrous oxalate, but is not limited thereto.
[0035] In some embodiments, the molybdenum source includes (NH4)6Mo7O 24 4H2O and / or potassium molybdate, but not limited thereto.
[0036] In some embodiments, the phosphorus source includes one or more of NH4H2PO4, (NH4)2HPO4, ammonium phosphate, phosphorus pentoxide, and potassium dihydrogen phosphate, but is not limited thereto.
[0037] The third object of the present invention is to provide a heterogeneous structure material, which is prepared by the method described in any of the above technical solutions.
[0038] A fourth object of the present invention is to provide an application of a heterostructure material in the preparation of a positive electrode for a sodium ion battery or a sodium ion battery.
[0039] A fifth object of the present invention is to provide a positive electrode for a sodium ion battery, comprising a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, wherein the positive electrode active material layer comprises the heterostructure material.
[0040] In some embodiments, the positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder in a mass ratio of 90 to 99: 0.5 to 5: 0.5 to 5, and the positive electrode active material includes the heterostructure material. The conductive agent and binder used can be any conductive material and binder material currently used in secondary batteries, for example, the conductive agent includes conductive carbon black, and the binder includes a combination of one or more of sodium carboxymethyl cellulose, styrene butadiene latex, and polyvinylidene fluoride, but is not limited thereto.
[0041] The positive electrode current collector may be any positive electrode current collector currently used in sodium ion batteries, for example, a metal foil, the material of the metal foil including, for example, aluminum and / or copper.
[0042] In some embodiments, a positive electrode slurry containing a positive electrode active material, a conductive agent and a binder is coated on the surface of the positive electrode current collector to form a positive electrode of a sodium ion battery, and the positive electrode active material includes the heterostructure material.
[0043] The sixth object of the present invention is to provide a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode is the positive electrode for the sodium ion battery described in any one of the technical solutions.
[0044] Compared with the prior art, the present invention has at least the following beneficial effects:
[0045] (1) The present invention composites a potassium ion conductor material with a wide alkali metal ion channel and high conductivity on the surface of a sodium-based layered oxygen cathode material, and the obtained heterostructure material has better electrical conductivity and ion conductivity; the composite of the potassium ion conductor and the sodium-based layered oxide is not a simple coating, but two materials with similar ion channels are sintered at high temperature to form a heterostructure material, and the two ion channels form a sodium-potassium solid solution at the composite and are connected, so that the heterostructure material has a significant improvement in electrochemical performance compared to the layered oxygen cathode material not composited with the potassium ion conductor, which is specifically manifested in that the rate performance and cycle performance have been significantly improved;
[0046] (2) The potassium ion conductor composited on the surface also plays a certain role as a coating material, which can inhibit the contact between the layer oxygen material and the outside world, further improving the chemical stability and cycle performance of the heterostructure material. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0048] Figure 1 This is an electron microscope image of the heterostructure material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0049] As used herein:
[0050] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0051] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0052] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0053] In these examples, parts and percentages are by mass unless otherwise indicated.
[0054] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0055] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0056] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0057] The experimental materials used in the following examples, unless otherwise specified, can be purchased from conventional biochemical reagent companies. Unless otherwise specified, "room temperature" used in this application refers to the temperature measured by a Celsius thermometer in an ordinary laboratory, generally 20-30°C, preferably 25°C (Kelvin temperature is 298.15K) ± 2°C.
[0058] Example 1
[0059] With KNO3, Fe(NO3)3·9H2O, NH4H2PO4, (NH4)6Mo7o 24 4H2O as a raw material, and weighing each raw material according to the molar ratio in the chemical formula K2Fe2(Moo4)(PO4)2; dissolving each weighed raw material in deionized water and stirring continuously, and continuously dropping 68.0% concentrated sulfuric acid, the total dropping amount of which is about 0.2wt% of the total mass of the above raw materials, so that the above raw materials are completely dissolved to obtain a mixed solution; drying the obtained mixed solution to form a dry gel with a water content of about 1wt%;
[0060] A spherical hydroxide precursor with a ratio of Ni:Fe:Mn=1:1:1 was prepared by coprecipitation method. The precursor, sodium carbonate and cobalt oxide were mixed according to the chemical formula NaNi 0.33 Fe 0.33 Mn 0.33 Co 0.01 The molar ratio of O2 is weighed and mixed evenly, and sintered at 500°C for 8h to obtain a sodium-based layered oxide pre-drive;
[0061] The sodium-based layered oxide precursor and the dry gel obtained above were uniformly mixed in a mass ratio of 100:5, and powdered in a powder mill at a speed of 30000 r / min for 30 seconds, and then sintered at a temperature of 850° C. for 20 hours to obtain a heterogeneous structure material composited with sodium-based layered oxide and potassium ion conductor.
[0062] Figure 13 is an electron microscope image of the heterogeneous structure material obtained in this embodiment. It can be seen from the image that the heterogeneous structure material as a whole is presented as spherical particles. The black part in the center of the spherical particles is a sodium-based spherical oxide, the white part on the surface is a potassium ion conductor, and the gray area at the junction of black and white is the composite interface of the two, which is a sodium-potassium solid solution.
[0063] The preparation of a sodium ion battery using the above heterogeneous structure material specifically includes the following steps:
[0064] The heterogeneous structure material, binder PVDF and conductive agent were mixed in a mass ratio of 90:5:5 to form a positive electrode slurry, which was coated on an aluminum foil to form a positive electrode sheet; the negative electrode was sodium, the electrolyte was NaPF6-diethylene glycol dimethyl ether (DIGLYME) electrolyte, the battery shell model was CR2032, and they were assembled into a sodium ion battery. The relevant performance tests of the sodium ion battery were carried out, and the results are shown in Table 1.
[0065] Example 2
[0066] With KNO3, Fe(NO3)3·9H2O, NH4H2PO4, (NH4)6Mo7O 24 4H2O is used as a raw material, and each raw material is weighed according to the molar ratio in the chemical formula KFe2(MoO4)2(PO4); each weighed raw material is dissolved in deionized water and stirred continuously, and concentrated sulfuric acid with a concentration of 68.0% is continuously added dropwise, and the total amount of the added dropwise amount is about 1.0wt% of the total mass of the raw materials so that the above raw materials are completely dissolved to obtain a mixed solution; the obtained mixed solution is dried to form a dry gel with a water content of about 2wt%;
[0067] A spherical hydroxide precursor with a ratio of Ni:Fe:Mn:Cu=2:3:3:1 was prepared by coprecipitation method. The precursor and sodium carbonate were mixed according to the chemical formula Na 0.9 Ni 0.22 Fe 0.33 Mn 0.33 Cu 0.11 The molar ratio of O2 is weighed and mixed evenly, and sintered at 600°C for 6 hours to obtain a sodium-based layered oxide pre-drive;
[0068] The sodium-based layered oxide precursor and the dry gel obtained above were uniformly mixed in a mass ratio of 100:2, powdered in a powder mill at a speed of 30000 r / min for 30 seconds, and sintered at a temperature of 900° C. for 15 hours to obtain a heterogeneous structure material composited with sodium-based layered oxide and potassium ion conductor.
[0069] The same method as in Example 1 was used to prepare the positive electrode sheet, and the sodium ion battery was assembled and tested for relevant performance. The results are shown in Table 1.
[0070] Example 3
[0071] With KNO3, Fe(NO3)3·9H2O, NH4H2PO4, (NH4)6Mo7O 24 4H2O as a raw material, and weighing each raw material according to the molar ratio in the chemical formula KFe2(MoO4)2(PO4); dissolving each weighed raw material in deionized water and stirring continuously, and continuously adding concentrated sulfuric acid with a concentration of 68.0%, and the total amount of the added dropwise addition is about 1.0wt% of the total mass of the above raw materials, so that the above raw materials are completely dissolved to obtain a mixed solution; drying the obtained mixed solution to form a dry gel with a water content of about 2wt%;
[0072] A spherical hydroxide precursor with a ratio of Ni:Fe:Mn:Zn=2:3:4:1 was prepared by coprecipitation. The precursor and sodium carbonate were mixed according to the chemical formula Na 0.95 Ni 0.2 Fe 0.3 Mn 0.4 Zn 0.1 The molar ratio of O2 is weighed and mixed evenly, and sintered at 400°C for 15h to obtain a sodium-based layered oxide pre-drive;
[0073] The sodium-based layered oxide precursor and the dry gel obtained above were uniformly mixed in a mass ratio of 100:1, powdered in a powder mill at a speed of 30000 r / min for 30 seconds, and sintered at a temperature of 950°C for 12 hours to obtain a heterogeneous structure material composite of sodium-based layered oxide and potassium ion conductor.
[0074] The same method as in Example 1 was used to prepare the positive electrode sheet, and the sodium ion battery was assembled and tested for relevant performance. The results are shown in Table 1.
[0075] Example 4
[0076] With KNO3, Fe(NO3)3·9H2O, NH4H2PO4, (NH4)6Mo7O 24 4H2O as a raw material, and weighing each raw material according to the molar ratio in the chemical formula K2Fe2(MoO4)(PO4)2; dissolving each weighed raw material in deionized water and stirring continuously, and continuously adding concentrated sulfuric acid with a concentration of 68.0%, and the total amount of the added dropwise addition is about 0.2wt% of the total mass of the raw material to completely solvent-heat the above raw materials, to obtain a mixed solution; drying the obtained mixed solution to form a dry gel with a water content of about 1wt%;
[0077] A spherical hydroxide precursor with a ratio of Ni:Fe:Mn=1:1:2 was prepared by coprecipitation method. The precursor, sodium carbonate, titanium oxide, magnesium oxide and calcium oxide were mixed according to the chemical formula Na 0.75 Ni 0.2Fe 0.2 Mn 0.4 Mg 0.06 Ti 0.1 Ca 0.04 The molar ratio of O2 is weighed and mixed evenly, and sintered at 600°C for 16 hours to obtain a sodium-based layered oxide pre-drive;
[0078] The sodium-based layered oxide precursor and the dry gel obtained above were uniformly mixed in a mass ratio of 100:0.5, powdered in a powder mill at a speed of 30000 r / min for 30 seconds, and sintered at a temperature of 1000° C. for 6 hours to obtain a heterogeneous structure material composite of sodium-based layered oxide and potassium ion conductor.
[0079] The same method as in Example 1 was used to prepare the positive electrode sheet, and the sodium ion battery was assembled and tested for relevant performance. The results are shown in Table 1.
[0080] Example 5
[0081] Example 5 is substantially the same as Example 1, except that, in Example 5, the sodium-based layered oxide precursor and the dry gel are uniformly mixed in a mass ratio of 100:0.2 to prepare a heterostructure material.
[0082] Example 6
[0083] Example 6 is substantially the same as Example 1, except that, in Example 6, the sodium-based layered oxide precursor and the dry gel are uniformly mixed in a mass ratio of 100:10 to prepare a heterogeneous structure material.
[0084] Comparative Example 1
[0085] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 2, only sodium-based layered oxide is used as the positive electrode active material of the sodium ion battery. The preparation method of the sodium-based layered oxide is as follows:
[0086] A spherical hydroxide precursor with a ratio of Ni:Fe:Mn=1:1:1 was prepared by coprecipitation method. The precursor, sodium carbonate and cobalt oxide were mixed according to the chemical formula NaNi 0.33 Fe 0.33 Mn 0.33 Co 0.01 O2 is weighed and mixed evenly, and sintered at 500℃ for 8h to obtain a sodium-based layered oxide pre-drive;
[0087] The sodium-based layered oxide precursor obtained above was powdered in a powder mill at a speed of 30000 r / min for 30 seconds, and then sintered at a temperature of 850° C. for 20 hours to obtain a sodium-based layered oxide.
[0088] The preparation of the sodium ion battery of Comparative Example 1 is different from that of Example 1 only in that the heterostructure material used in the preparation of the positive electrode of Example 1 is replaced with the sodium-based layered oxide material of this comparative example, and the rest is the same as Example 1.
[0089] Comparative Example 2
[0090] Comparative Example 2: A mixture of a potassium ion conductor and a sodium-based layered oxide that has been simply mixed is used as the active material of a sodium ion battery, specifically comprising:
[0091] With KNO3, Fe(NO3)3·9H2O, NH4H2PO4, (NH4)6Mo7O 24 ·4H2O is used as a raw material, and each raw material is weighed according to the molar ratio in the chemical formula K2Fe2(MoO4)(P04)2; each weighed raw material is dissolved in deionized water and continuously stirred, and concentrated sulfuric acid with a concentration of 68.0% is continuously added dropwise, and the total amount of the added dropwise amount is about 0.2wt% of the total mass of the above raw materials so that the above raw materials are completely dissolved to obtain a mixed solution; the obtained mixed solution is dried to form a dry gel with a water content of about 1wt%; the dry gel is powdered in a powdering machine at a speed of 30000r / min for 30s, and then sintered at a temperature of 850°C for 20h to obtain a potassium ion conductor.
[0092] A spherical hydroxide precursor with a ratio of Ni:Fe:Mn=1:1:1 was prepared by coprecipitation method. The precursor, sodium carbonate and cobalt oxide were mixed according to the chemical formula NaNi 0.33 Fe 0.33 Mn 0.33 Co 0.01 O2 is weighed and mixed evenly, and sintered at 500°C for 8 hours to obtain a sodium-based layered oxide pre-driven material; the sodium-based layered oxide pre-driven material obtained above is powdered in a powder mill at a speed of 30000r / min for 30s, and sintered at 850°C for 20 hours to obtain a sodium-based layered oxide.
[0093] The sodium-based layered oxide prepared above and the potassium ion conductor are uniformly mixed in a mass ratio of 100:5 to form a mixture.
[0094] The preparation of the sodium ion battery of Comparative Example 2 is different from that of Example 1 only in that the heterostructure material in the preparation of the positive electrode of Example 1 is replaced with the mixture of this comparative example, and the rest is the same as Example 1. In Comparative Example 2, the simple mixing of the potassium ion conductor and the sodium-based layered oxide cannot form a sodium-potassium solid solution, and the potassium ion conductor cannot play a gain effect as an active material, but affects the battery performance.
[0095] Comparative Example 3
[0096] The only difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, the sodium-based layered oxide precursor and the dry gel are mixed uniformly at a mass ratio of 100:20 and then sintered, and the mass proportion of the potassium ion conductor in the obtained heterogeneous structure material is 10wt%, and the rest is the same as Example 1. It is found that compared with Example 1, the battery capacity and rate performance of Comparative Example 3 are reduced, which may be due to the large amount of potassium ion conductor and the thick coating layer formed.
[0097] Comparative Example 4
[0098] The only difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, the sodium-based layered oxide precursor and the dry gel are mixed uniformly at a mass ratio of 100:0.05 and then sintered, and the mass proportion of the potassium ion conductor in the obtained heterogeneous structure material is 0.05wt%, and the rest is the same as Example 1. It is found that compared with Example 1, the battery rate performance of Comparative Example 4 is reduced, which may be due to the low content of sodium-potassium solid solution formed when the amount of potassium ion conductor is low.
[0099] Table 2 Related performances of sodium ion batteries in the embodiments of the present invention and the comparative examples
[0100]
[0101]
[0102] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0103] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0104] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.
Claims
1. A heterogeneous structure material, characterized in that: The heterogeneous structure material comprises a composite sodium-based layered oxide and a potassium ion conductor, wherein the potassium ion conductor is loaded on the surface of the nano-based layered oxide, and a sodium-potassium solid solution is formed at the composite interface between the two. The chemical formula of the sodium-based layered oxide is Na x Ni a Fe b Mn c M d O2, wherein a+b+c+d=1, 0.7≤x≤1.0, 0.1≤a≤0.4, 0.1≤b≤0.4, 0.2≤c≤0.6, 0.01≤d≤0.2, and M includes any one or more combinations of K, Li, Ca, Cu, Mg, Zn, Sr, B, Y, Sn, Al, Nb, Ti, Zr, W, Sr, Co, and Mo elements; The chemical formula of the potassium ion conductor is K 1+z Fe2(MiI4) 2-z (Pi4) 1+z , 0≤z≤1.
2. The heterostructure material according to claim 1, characterized in that: The mass proportion of the potassium ion conductor in the heterostructure material is 0.1% to 5.0%; And / or, the mass proportion of the sodium-potassium solid solution in the heterostructure material is 0.02% to 1.5%.
3. A method for preparing a heterogeneous structure material, characterized in that: include: Providing a sodium-based layered oxide precursor; drying a mixed solution containing a potassium source, an iron source, a molybdenum source and a phosphorus source to obtain a gel; The gel and the sodium-based layered oxide precursor are mixed and crushed to obtain a first mixture; The first mixture is subjected to a first sintering in an oxygen-containing atmosphere to form a heterogeneous structure material composed of a sodium-based layered oxide and a potassium ion conductor, wherein the heterogeneous structure material includes a sodium-potassium solid solution formed at a composite interface of the sodium-based layered oxide and the potassium ion conductor.
4. The preparation method according to claim 3, characterized in that: The preparation method of the sodium-based layered oxide precursor comprises: A first mixed reaction system containing a nickel source, a manganese source and an iron source is subjected to a coprecipitation reaction to obtain a nickel-iron-manganese-based precursor; a second mixture containing the nickel-iron-manganese-based precursor, an M source and a sodium source is subjected to a second sintering under an inert atmosphere to obtain the sodium-based layered oxide precursor; Alternatively, a second mixed reaction system containing a nickel source, a manganese source, an iron source and an M source is subjected to a coprecipitation reaction to obtain a nickel-iron-manganese-based precursor doped with the M element; and a third mixture containing the nickel-iron-manganese-based precursor doped with the M element and a sodium source is subjected to a third sintering under inert atmosphere conditions to obtain the sodium-based layered oxide precursor.
5. The preparation method according to claim 4, characterized in that: The M source is used to provide a doping element M, and the doping element M includes any one or more combinations of K, Li, Ca, Cu, Mg, Zn, Sr, B, Y, Sn, Al, Nb, Ti, Zr, W, Sr, Co, and Mo elements; and / or, the M source comprises any one or more combinations of sulfate, hydrochloride, nitrate, carbonate, acetate, oxide, sulfide, nitride or hydroxide of the doping element M; And / or, the sodium source includes any one or more combinations of anhydrous sodium carbonate, sodium carbonate monohydrate, sodium carbonate decahydrate, sodium bicarbonate or sodium sulfate; And / or, the nickel source, iron source, manganese source, M source are in accordance with the chemical formula of sodium-based layered oxide Na x Ni a Fe b Mn c M d The molar ratio of Ni, Fe, Mn and M in O2 is weighed, where a+b+c+d=1, 0.7≤x≤1.0, 0.1≤a≤0.4, 0.1≤b≤0.4, 0.2≤c≤0.6, 0.01≤d≤0.2; And / or, the process conditions of the second sintering and the third sintering include: a sintering temperature of 300-600° C. and a sintering time of 4-16 hours.
6. The preparation method according to claim 3, characterized in that: The preparation method of the mixed solution comprises: dispersing the potassium source, the iron source, the molybdenum source and the phosphorus source in a solvent, and then adding concentrated nitric acid with a concentration of 68.0wt% to 88.0wt% in batches under stirring, wherein the amount of the concentrated nitric acid added is 0.01 to 0.5wt% of the mixed solution, so that the potassium source, the iron source, the molybdenum source and the phosphorus source are completely dissolved to obtain the mixed solution; And / or, the drying dries the water content in the gel to 0.1-3 wt %; And / or, the process conditions of the first sintering include: a sintering temperature of 800 to 1000° C. and a sintering time of 6 to 20 hours; And / or, the pulverizing is performed by a powdering machine with a rotation speed of 10000 to 60000 r / min and a pulverizing time of 20 to 60 s; and / or, the mass ratio of the sodium-based structured oxide precursor to the gel in the first mixture is 100:0.2 to 100:10; And / or, the potassium source includes one or more of potassium nitrate, potassium carbonate, potassium hydroxide, potassium bicarbonate, potassium acetate, potassium dihydrogen phosphate, potassium citrate, and potassium oxalate; the iron source includes one or more of ferric nitrate, ferric acetate, ferric sulfate, and ferrous oxalate; the molybdenum source includes (NH4)6Mo7O 24 4H2O and / or potassium molybdate, the phosphorus source includes one or more of NH4H2PO4, (NH4)2HPO4, ammonium phosphate, phosphorus pentoxide, and potassium dihydrogen phosphate.
7. A heterogeneous structure material, characterized in that: The method is prepared by the method described in any one of claims 3 to 6.
8. Use of the heterostructure material according to claim 1, 2 or 7 in preparing a positive electrode for a sodium ion battery or a sodium ion battery.
9. A positive electrode for a sodium ion battery, comprising a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, characterized in that: The positive electrode active material layer comprises the heterostructure material according to claim 1, 2 or 7; Preferably, a positive electrode slurry containing a positive electrode active material, a conductive agent and a binder is coated on the surface of the positive electrode current collector to form a positive electrode of a sodium ion battery, wherein the positive electrode active material includes the heterostructure material; Preferably, the positive electrode active material layer comprises a positive electrode active material, a conductive agent and a binder in a mass ratio of 90 to 99: 0.5 to 5: 0.5 to 5, and the positive electrode active material comprises the heterogeneous structure material; Preferably, the conductive agent used in the positive electrode active material layer includes conductive carbon black, and the binder used in the positive electrode active material layer includes one or a combination of sodium carboxymethyl cellulose, styrene-butadiene latex, and polyvinylidene fluoride; And / or, the positive electrode current collector is a metal foil, and the material of the metal foil includes aluminum and / or copper.
10. A sodium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The positive electrode is the positive electrode for a sodium ion battery according to claim 9.